2007
DOI: 10.1039/b707524c
|View full text |Cite
|
Sign up to set email alerts
|

Reversible photopadlocking on double-stranded DNA

Abstract: We describe a highly efficient method for reversible photocircularization of oligonucleotide (ODN) on a double-stranded DNA template: 5-carboxyvinyl-2'-deoxyuridine-containing ODN was reversibly circularized around the target sequence of the double-stranded plasmid DNA resulting in formation of a catenated plasmid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…These modifications have been extensively explored and optimised for use in complex DNA systems, such as logic circuits, by the Fujimoto group. [107][108][109][110] The inclusion of electron-withdrawing groups (for example, carboxyl and cyanomoieties) further enhances reactivity; 111,112 enabling light manipulation of DNA structures, even for highly complex origami assemblies. 113 The cyanovinyl carbazole nucleoside is a commonly used photo-crosslinking modification in the field of nucleic acid chemistry.…”
Section: Vinyl Dna Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications have been extensively explored and optimised for use in complex DNA systems, such as logic circuits, by the Fujimoto group. [107][108][109][110] The inclusion of electron-withdrawing groups (for example, carboxyl and cyanomoieties) further enhances reactivity; 111,112 enabling light manipulation of DNA structures, even for highly complex origami assemblies. 113 The cyanovinyl carbazole nucleoside is a commonly used photo-crosslinking modification in the field of nucleic acid chemistry.…”
Section: Vinyl Dna Modificationsmentioning
confidence: 99%
“…In addition to the development of the cyanovinyl carbazole, Fujimoto's group evaluated the commercially available 5-carboxyvinyl-2′-deoxyuridine as a photo-crosslinking modification. 108 They demonstrated that 5-carboxyvinyl-2′-deoxyuridine could be used to photo-ligate two ends of an oligonucleotide to form a cyclic oligonucleotide. By irradiating at 366 nm, these artificial nucleotides produced photo-ligated catenated sequences with high efficiency without any side reactions.…”
Section: Cyclobutane Pyrimidine Dna Modificationsmentioning
confidence: 99%
“…Therefore, these authors succeeded in developing a reversible photoligation method by switching between irradiation at two wavelengths. Furthermore, they improved the photoactivation reagent and reported a photoligation reaction using 5'-carboxyvinyldeoxyuridine [15,16,17,18,19,20,21]. The irradiation of these probes at 366 nm for 1 h in the presence of template resulted in the expected ligation product, with a yield of 93%.…”
Section: The Templated Photochemical Reactionmentioning
confidence: 99%
“…The irradiation of these probes at 366 nm for 1 h in the presence of template resulted in the expected ligation product, with a yield of 93%. These authors applied these probes to the detection of single-base mismatches [19,22,23,24,25], the formation of various special structures [13,14,15,17,21,26,27], the site-specific transition of cytosine to uracil [16,28,29], and the development of DNA computing [18].…”
Section: The Templated Photochemical Reactionmentioning
confidence: 99%
“…143 -146 Much work in the fi eld is based on the [2 + 2] cycloaddition between uridine derivatives developed by Fujimoto and coworkers. 147 -149 The method relies on a modifi ed uridine in which the chromophore ' s absorption envelope is extended into the visible by conjugation and is applicable to circular DNA 150 and RNA. 151,152 A particularly interesting aspect is that the photoligation can be made reversible under the irradiation conditions by using a tethered carbazole PET sensitizer.…”
Section: Photoligation Of Oligonucleotides In Solutionmentioning
confidence: 99%